2018
DOI: 10.22452/mjlis.vol23no2.5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of interdisciplinary research in author keywords appearing in Korean journals

Abstract: Keywords for academic papers are terms selected and created by the authors, and are, in general, considered a core element that summarizes and represents the papers' content. This research analysed the ways in which the author keywords for academic papers are used in multiple disciplines. The Brillouin index was used for an analysis of interdisciplinarity. As a result, 63.7 percent of the keywords were shown to appear in only one area of study. These cannot be considered keywords with interdisciplinarity, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Co-occurrence analysis develops thematic links with other keywords to identify the general themes of a discipline. Usually, these keywords are regarded as core elements, which conceptualize and summarize the content of scientific publications (Kwon, 2018) for scientific development. The “co-occurrence of keywords” conveys the “frequency of keywords” in which the keywords occur “next to other keywords” in the publications.…”
Section: Resultsmentioning
confidence: 99%
“…Co-occurrence analysis develops thematic links with other keywords to identify the general themes of a discipline. Usually, these keywords are regarded as core elements, which conceptualize and summarize the content of scientific publications (Kwon, 2018) for scientific development. The “co-occurrence of keywords” conveys the “frequency of keywords” in which the keywords occur “next to other keywords” in the publications.…”
Section: Resultsmentioning
confidence: 99%
“…For understanding to what extent author keyword in an academic paper can be considered as a key element to understand the contents of the paper, Kwon, [38] using Brillouin Index, found that the interdisciplinarity degree of 80% of the keywords were as low as 0 to 0.499. The interdisciplinarity of author keywords in physical education was the least followed by social sciences and humanities.…”
Section: Text Analysis-researchesmentioning
confidence: 99%
“…We want to highlight that the keyword 'international airport' appeared in the 95th position (6 occurrences 6 and a link strength of 22) among the 116 remaining keywords. Airport, model, and airlines are keywords regularly used in the Journal of Air Transport Management because these are related with the citation counts of papers [11,93,94]. Figure 3 illustrates the heterogeneity of universities and countries where work on the IAA topic was posted.…”
Section: Most Frequent Abstract In the Iaa Topicmentioning
confidence: 99%